2015
DOI: 10.1097/md.0000000000002242
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prolonged Postoperative Ileus After Radical Gastrectomy for Gastric Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 40 publications
6
32
5
Order By: Relevance
“…There is no universally accepted clinical definition for POI, and PPOI is considered to be a more clinically problematic and pathologically significant entity [8]. In our study, there were no significant differences in the incidence of PPOI in the two groups.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…There is no universally accepted clinical definition for POI, and PPOI is considered to be a more clinically problematic and pathologically significant entity [8]. In our study, there were no significant differences in the incidence of PPOI in the two groups.…”
Section: Discussioncontrasting
confidence: 39%
“…In the IVPCA group, the patients received a basal infusion of 1 ml/h with boluses of 1 ml and a lockout interval of 15 minutes using a pump (Autoselector; Ace Medical Co., Ltd., Korea) containing 100 ml of a solution containing fen- [7]. Prolonged postoperative ileus (PPOI) was defined as a situation wherein two or more of the following was present: nausea, inability to tolerate oral diet over 24 hours, absence of flatus over 24 hours, abdominal distension, and radiological confirmation on or after the fourth POD without prior resolution of postoperative ileus (POI) [8]. Delirium was assessed using medical records.…”
Section: Methodsmentioning
confidence: 99%
“…A large‐scale observational study of patients who underwent colorectal cancer surgeries (n = 2400) showed an insignificant association between age and mechanical bowel obstruction but did not cite the need of surgery for mechanical bowel obstruction . However, in other studies, age was an independent risk factor for mechanical bowel obstruction and was included in the predictive scoring system . It may also be that intestinal movement is slower in elderly than in younger patients, such that the elderly are more likely to develop severe mechanical bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of them nor the current study demonstrated a significant association. The role of previous abdominal surgery in major abdominal surgeries was controversial: the association was significant in patients with laparoscopic colectomy but not in those with gastrectomy or colorectal resection …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PPOI was reported to vary from 3% to 32%, and there were some differences among the sites of abdominal surgery . However, a majority of the previous studies on PPOI were based on patients referred to colonic or rectal resection, and little data existed on gastrectomy …”
Section: Introductionmentioning
confidence: 99%